Gene Replacement in Arabidopsis Reveals Manganese Transport as an Ancient Feature of Human, Plant and Cyanobacterial UPF0016 Proteins - Hoecker, Natalie; Hennecke, Yvonne; Schrott, Simon; Marino, Giada; Schmidt, Sidsel Birkelund; Leister, Dario; Schneider, Anja (Frontiers in Plant Science, 2021)
The protein family 0016 (UPF0016) is conserved through evolution, and the few members characterized share a function in Mn2+ transport. So far, little is known about the history of these proteins in Eukaryotes. In Arabidopsis thaliana five such proteins, comprising four different subcellular localizations including chloroplasts, have been described, whereas non-photosynthetic Eukaryotes have only one. We used a phylogenetic approach to classify the eukaryotic proteins into two subgroups and performed gene-replacement studies to investigate UPF0016 genes of various origins. Replaceability can be scored readily in the Arabidopsis UPF0016 transporter mutant pam71, which exhibits a functional deficiency in photosystem II. The N-terminal region of the Arabidopsis PAM71 was used to direct selected proteins to chloroplast membranes. Transgenic pam71 lines overexpressing the closest plant homolog (CMT1), human TMEM165 or cyanobacterial MNX successfully restored photosystem II efficiency, manganese binding to photosystem II complexes and consequently plant growth rate and biomass production. Thus AtCMT1, HsTMEM165 and SynMNX can operate in the thylakoid membrane and substitute for PAM71 in a non-native environment, indicating that the manganese transport function of UPF0016 proteins is an ancient feature of the family. We propose that the two chloroplast-localized UPF0016 proteins, CMT1 and PAM71, in plants originated from the cyanobacterial endosymbiont that gave rise to the organelle.